Comment on a generalized stochastic restricted ridge regression estimator. Issue 10 (19th May 2017) - Kaçiranlar, Selahattin; Dawoud, Issam
ABSTRACT: In this note, we make some comments about the paper of Alheety and Kibria (2014 ) and correct the wrongly proved Theorems in that paper.